2021
DOI: 10.3390/diagnostics11030449
|View full text |Cite
|
Sign up to set email alerts
|

Latest Insights into Mechanisms behind Atrial Cardiomyopathy: It Is Not always about Ventricular Function

Abstract: Atrial cardiomyopathy (ACM) represents a constantly evolving concept, with increasing importance in contemporary research and clinical practice. A better understanding of the mechanisms involved in atrial remodeling and its clinical correlations especially with atrial fibrillation (AF) and other cardiometabolic comorbidities may induce a significant impact on the diagnosis, prognosis, and therapeutic approach of ACM-related comorbidities. Although initially described several decades ago, investigators have onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…Our results showed that sST2 is associated with increased LV filling pressures (expressed as E/e'), but not with an increased LA volume, a finding similar to those from other studies [19,20], but opposed to the results obtained by Najjar et al who found a correlation between sST2 and LA indexed volume, but not with E/e' [10]. However, LA strain-as a possible source for sST2 release-is independent of LA volume, as the LA fibrosis and the subsequent atrial cardiomyopathy are rather related to different pathophysiological pathways (e.g., inflammation, oxidative stress, electrical alterations), as shown in PARAMOUNT trial and other literature data [21,22]. We did not notice any association between sST2 and LVEF, a finding that is consistent with some previous literature data [10,23], but discordant to studies that highlighted an association between increased sST2 and reduced LVEF following an acute myocardial infarction [24] or in patients with acute onset dyspnea [25,26].…”
Section: Discussionmentioning
confidence: 59%
“…Our results showed that sST2 is associated with increased LV filling pressures (expressed as E/e'), but not with an increased LA volume, a finding similar to those from other studies [19,20], but opposed to the results obtained by Najjar et al who found a correlation between sST2 and LA indexed volume, but not with E/e' [10]. However, LA strain-as a possible source for sST2 release-is independent of LA volume, as the LA fibrosis and the subsequent atrial cardiomyopathy are rather related to different pathophysiological pathways (e.g., inflammation, oxidative stress, electrical alterations), as shown in PARAMOUNT trial and other literature data [21,22]. We did not notice any association between sST2 and LVEF, a finding that is consistent with some previous literature data [10,23], but discordant to studies that highlighted an association between increased sST2 and reduced LVEF following an acute myocardial infarction [24] or in patients with acute onset dyspnea [25,26].…”
Section: Discussionmentioning
confidence: 59%
“…In remote locations or in circumstances when echocardiography is unavailable, these new biomarkers can be used either independently or in a multi-marker battery test with NT-proBNP, adding diagnosis and prognosis value when compared to NT-proBNP alone. Moreover, the biomarkers’ value in predicting subclinical HF in patients with preserved LVEF (HFpEF) is also highlighted in a recent review, showing that elevated serum levels of both NT-proBNP and ST2 are suggestive for atrial remodeling, which is often a preliminary morphological step before clinically manifest ventricular dysfunction [ 33 ]. Our results show that sST2′s serum levels are very well corelated both with the symptomatology (expressed as dyspnea of NYHA III/IV class), echocardiographic aspects suggestive for HF, and NT-proBNP levels, but independent in relation to classical SES indicators.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is difficult to strictly correlate the presence of COVID-19 with the cardiovascular lesions evolving with increased biomarkers. Multiple studies have shown that elevated serum levels of cTn or NT-proBNP are similarly associated with a poor prognosis in a plethora of potentially COVID-19-related pathologies, such as pneumonia, septic shock, or acute respiratory distress syndrome [ 88 , 167 , 168 ]. For example, patients with pneumonia who had elevated concentrations of NT-proBNP were more prone to be admitted to ICU wards, regardless of the presence of cardiac dysfunction.…”
Section: Biomarkers In the Diagnosis And Prognosis Of Acute Myocardia...mentioning
confidence: 99%
“…For example, patients with pneumonia who had elevated concentrations of NT-proBNP were more prone to be admitted to ICU wards, regardless of the presence of cardiac dysfunction. There is growing evidence supporting the hypothesis of hypoxia-induced vasoconstriction that ultimately leads to pulmonary hypertension, which in turn may increase parietal RV stress in patients with extensive pulmonary lesions, thereby causing an increased NT-proBNP release from cardiomyocytes, a very plausible mechanism in the context of COVID-19 [ 168 , 169 , 170 ]. An additional inducer of myocardial parietal stress may be the widespread use of vasopressors in patients with septic shock, while acute kidney injury in severely ill patients may alter the clearance of NT-proBNP, leading to a false, non-cardiac increase in these biomarkers [ 88 , 170 ].…”
Section: Biomarkers In the Diagnosis And Prognosis Of Acute Myocardia...mentioning
confidence: 99%